Factors affecting job happiness among staff at Kolej Profesional Mara, Seri Iskandar, Perak - Mohd Ani, Mohd Aminuddin; Merican, Yasmine (2015)
Job happiness is one of the most desire factors and need to be nurtured in the organization as to reach new level of success. It drives many of us in our daily lives but often takes a back seat at work. This study analyzes the factors affecting job happiness among staff at Kolej Profesional MARA Seri Iskandar. It focuses on the organizational support, appreciation, work design and teamwork among staff. Data were collected and analyzed using Pearson Correlation, multiple regressions; mean score of T-test and ANOVA. The findings indicate that all four variables are positively correlated with the job happiness at different level. The predictor to the job happiness can be explained by the significant value of teamwork and organizational support only. The data analysis also revealed that there is no significant difference between gender with job happiness and its elements.However by looking at the group of department, there are significant differences of mean score for opinion on appreciation, teamwork and job happiness. Implications of the research, there are several recommendations that have been suggested in order to increase the level of job happiness among staff at Kolej Profesional MARA Seri Iskandar.